2006
DOI: 10.1088/0963-0252/15/2/005
|View full text |Cite
|
Sign up to set email alerts
|

Properties of an atmospheric pressure radio-frequency argon and nitrogen plasma

Abstract: An atmospheric pressure capacitive discharge source has been developed that operates at power densities over 100 W cm −3. The ground state nitrogen atom concentration was measured at the exit of the source by titration with NO, and it was found to reach a maximum of 3.0 ± 0.8 × 10 17 cm −3 at 6.0 vol% N 2 in argon, 250 • C and 150 W cm −3. This is equivalent to 2.3 vol% of N atoms in the afterglow. At these conditions, the electron density and temperature are estimated to be 3.1 × 10 12 cm −3 and 1.2 eV. A plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(76 citation statements)
references
References 48 publications
5
71
0
Order By: Relevance
“…Titration with a flow-tube reactor is commonly applied as a reference source for calibration [20]. Recently it was shown that a titration scheme allows a spatially not resolved measurement of the atomic nitrogen concentration in the effluent of a similar discharge [21]. The results presented here are based on a TALIF calibration scheme with xenon as described in greater detail in [8].…”
Section: Two-photon Absorption Laser-induced Fluorescencementioning
confidence: 99%
“…Titration with a flow-tube reactor is commonly applied as a reference source for calibration [20]. Recently it was shown that a titration scheme allows a spatially not resolved measurement of the atomic nitrogen concentration in the effluent of a similar discharge [21]. The results presented here are based on a TALIF calibration scheme with xenon as described in greater detail in [8].…”
Section: Two-photon Absorption Laser-induced Fluorescencementioning
confidence: 99%
“…The details of the transport coefficients and chemical reactions can be found in Ref. 19. Figure 1 shows the spatio-temporal profiles of the electron impact ionization rate and electron power absorption in the dual-frequency Ar DBD plasma as a function of the applied low frequency voltage amplitudes (from V lf =100 V to V lf =500 V).…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…Feed gas made of argon (or helium) and up to 0.1 vol% of other gases, flows between the electrodes at a rate of 20 up to 60 L/min. The gas emerges from the holes and impinges on a substrate placed 2 to 15 mm downstream, where cleaning or etching of surface material takes place [12].…”
Section: Fluid Dynamicsmentioning
confidence: 99%
“…Although there exists advanced experimental and modelling studies a complete picture of the physical and chemical processes determining the performance of this discharge is not obtained, yet. Most of the studies are on the gas breakdown [7][8][9], the transitions of the discharge from  to  mode [10,11] and the concentration of radicals in the afterglow [12,13].…”
Section: Introductionmentioning
confidence: 99%